A Gender Performativity in Movie 'Clueless' (1995) Based on Judith Butler's Approach: A Feminist Analysis of Gender Construction Through Fashion and Identity - Lenni herawati Sirait; Berlian Hasian Keyla Sinambela; T Muhammad Raihan Fadillah; Rahmadsyah Rangkuti (UPT P2M Politeknik Negeri Malang, 2025)
This study analyzes the 1995 film Clueless through Judith Butler's theory of gender performativity, which views gender as a construct shaped by societal expectations and repetitive actions. Using qualitative analysis, the research highlights how the film critiques traditional gender norms through its characters. Cher’s hyperfemininity both adheres to and challenges societal expectations, Tai’s fashion-driven transformation reflects identity fluidity, and Christian’s ambiguous masculinity subverts conventional norms. Additionally, humor in the film critiques class and gender constructs. The study situates Clueless within feminist and demonstrating how it portrays gender as dynamic and open to reinterpretation.